Overcoming Mohs Limitations in Treating DFSP: Retrospective Analysis of a Novel Excision Technique - Rami Shoufani; Ariel Berl; Ofir Shir-az; Deborah Kidron; Din Mann; Noam Castel; Avshalom Shalom (Life)
Dermatofibrosarcoma protuberans (DFSP) is a rare, soft-tissue sarcoma characterized by dermal, finger-like projections and high local recurrence rates. Complete surgical excision is the primary treatment goal and Mohs micrographic surgery (MMS) is the accepted approach for achieving disease-free margins. Despite the effectiveness of MMS, it has limitations when treating DFSP, with documented local recurrences. This paper presents our experience and treatment modality for DFSP, using MMS with an additional “safety margin”. This technique seeks to ensure free surgical margins and potentially lower recurrence rates. This is a retrospective analysis of patients treated for DFSP over a 10-year period. All patients underwent MMS, followed by an additional, circumferential excision of 2–5 mm. Twenty-two patients were treated surgically for DFSP from 2014 to 2023. The median age at presentation was 42.5 years. Four patients (18%) had positive disease margins on the additional safety marginal excision, two had negative MMS slides, and the other two were positive for DFSP. The mean follow-up time was 27 months, and no local recurrences were observed during that time. The surgical method presented here includes an additional excision of the surrounding margins following MMS for DFSP. This technique provides a tool to overcome the limitations of MMS in treating this tumor, aiming to reduce local recurrence.